Obama's wars / Bob Woodward. - Woodward, Bob, 1943- (New York : Simon & Schuster, 2010)
Woodward shows Obama making the critical decisions on the Afghanistan War, the secret war in Pakistan and the worldwide fight against terrorism.
Book with ISBN 9781849832205 is published in London, 2011.
Includes bibliographical references (p. [391]-416) and index.
Keywords: Obama, Barack -- Military leadership; National security -- United States -- Decision making; Afghan War, 2001- -- United States; War on Terrorism, 2001-2009.; United States -- Military policy -- Decision making; Pakistan -- Military relations -- United States; United States -- Officials and employees -- Interviews